Analisis pemenuhan standar nasional pendidikan dan permasalahannya - Yulius Mataputun (Jurnal Konseling dan Pendidikan, 2020)
This study aims to analyze the fulfillment of the National Education Standards (SNP) and its problems in Papuan SMTKs. The research method used is a mixed method. The research subjects were 33 heads of Papuan SMTKs, heads of Christian education, and assessors of BAN-S / M Papua. Data collection used the 2017 SMA / MA accreditation instruments, interviews, and documentation. The data analysis technique used descriptive and interactive statistical tests by Miles and Huberman. The results showed that most of the Papuan SMTK had fulfilled the SNP. The Sapras and Tendik standards are still problematic because half of the SMTKs has not yet reached the SNP, even most of the SMTKs do not have biology, physics, chemistry, canteen, supervisors, administrative staff, administrative staff, and special service officers according to the SNP.